2012
DOI: 10.1021/ja308357y
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Surfactant-Type Catalyst for Asymmetric Reduction of Aliphatic Ketones in Water

Abstract: A novel chiral surfactant-type catalyst is developed. Micelles formed in water by association of the catalysts themselves, and this was confirmed by TEM analyses. Asymmetric transfer hydrogenation of aliphatic ketones catalyzed by the chiral metallomicellar catalyst gave good to excellent conversions and remarkable stereoselectivities (up to 95% ee). Synergistic effects between the metal-catalyzed center and the hydrophobic microenvironment of the core in the metallomicelle led to high enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 44 publications
2
93
1
1
Order By: Relevance
“…Many of these compounds comprise com plexes with Cp (cyclopentadienyl anion) due to their sufficient stability in protonic solvents, ultimately in water. Li et al described a Rh Cp I SURF used in enantioselective catalysis [42]. An inverted, hydropho bic hydrophilic motif was presented by Shen et al with an I SURF con taining ferrocene in the hydrophobic moiety [43].…”
Section: Amphiphilic Ligands With Coordinated Metalsmentioning
confidence: 99%
“…Many of these compounds comprise com plexes with Cp (cyclopentadienyl anion) due to their sufficient stability in protonic solvents, ultimately in water. Li et al described a Rh Cp I SURF used in enantioselective catalysis [42]. An inverted, hydropho bic hydrophilic motif was presented by Shen et al with an I SURF con taining ferrocene in the hydrophobic moiety [43].…”
Section: Amphiphilic Ligands With Coordinated Metalsmentioning
confidence: 99%
“…However, liquid inorganic acids inevitably have many disadvantages, such as corrosion of equipment, troublesome product separation and environmental pollution (4); and solid acids have also shown some disadvantages, including low activity, easy deactivation and adsorption of products (3,5). To address the drawbacks of both liquid and solid acids, a novel catalytic system, for example, colloidal dispersion or reverse micelles, formed by Brønsted acidsurfactant-combined catalyst, has been reported (6). For example, Kabayashi et al reported dodecylbenzene sulfonic acid (DBSA)-catalyzed esterification of carboxylic acids and alcohols in water (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In 2001 the first example of Ru(II)-catalyzed ATH of ketones with HCO 2 Na as a hydride source in aqueous media was reported [17]. Since this discovery, a number of water-soluble ligands and catalysts have been developed for ATH in aqueous media providing the reduction products in high conversion yields and enantioselectivities [18][19][20][21][22][23][24][25][26]. However, a major problem associated with these catalytic systems is that the low substrate/catalyst (S/C) ratio (normally S/C = 100) and large excess amounts of hydride donor (≥ 5 equiv.…”
Section: Introductionmentioning
confidence: 99%